Formulation and Characteristics of Nanostructured Lipid Carrier (NLC) Red Palm Oil (RPO) Prepared by High-Pressure Homogenization and Its Applications in Orange Juice - Wahid Wirawan; Sri Raharjo; Supriyadi Supriyadi (Indonesian Association of Food Technologists, 2022)
A Nanostructured lipid carrier (NLC) is an emulsion system that can encapsulate and improve stability of lipid-based bioactive compounds. This study aimed to develop an optimal RPO-NLC formula with a combination of solid and liquid lipids, lipids and surfactants, and the use of high-pressure homogenizer (HPH). RPO-NLC was made using HPH with a 400 bar and 600 bar pressure. A Completely randomized design (CRD) with three factors was used to determine interactions between factors. The RPO-NLC formula was characterized based on particle size. One of the best formulas was selected with small particle size and high RPO content then characterized based on encapsulation efficiency (EE), loading capacity (LC), storage stability, FTIR, thermal and applied to orange juice including sensory evaluation, encapsulation stability and pH. RPO-NLC yielded particle size 44.9 nm, EE 99.9±0.02%, LC 4.9±0.001%, was stable on storage. β-carotene identified in RPO-NLC lipid matrix based on FTIR analysis and has good thermal stability based on differential scanning calorimeter analysis. Sensory evaluation showed changes in sensory attributes of color, aroma, taste during storage. Encapsulation stability showed significant increase during storage and pH measurement results also increased.